Investigating Customer Attitude Towards Functional Food And Purchase Intention - Lau, Yong Sheng (Universiti Malaysia Sarawak (UNIMAS), 2019)
The purpose of this research is to identify the relationship between consumer attitudes towards to functional food (reward, necessity, confidence and safety) and purchase intention among of the university students in Malaysia. The theory applied on this study is theory of reasoned action (TRA) which used to understand the consumer behavior with 200 respondents from University Malaysia Sarawak (UNIMAS). According to the findings, it shows that the confidence in functional food is the most significant impact on the purchase intention and followed by reward from consuming functional food. The limitation and recommendation are provided at the end of study for further development and improvement.